Towards Reviving Electroweak Baryogenesis with a Fourth Generation - Wei-Shu Hou; Masaya Kohda (Advances in High Energy Physics)
Electroweak baryogenesis is an attractive scenario for explaining the baryon asymmetry of the universe. However, it does not work within the standard model due to two reasons: (1) the strength of CP violation from the Kobayashi-Maskawa mechanism with three generations is too small; (2) the electroweak phase transition is not first order for the experimentally allowed Higgs boson mass. We discuss possibilities to solve these problems by introducing a fourth generation of fermions and how electroweak baryogenesis might be revived. We also discuss briefly the recent observation of a Higgs-like boson with mass around 125 GeV, which puts the fourth generation in a difficult situation, and the possible way out.